Novel 3D analysis of reduction behavior of single iron-oxide particle in CO-CO2 gas atmosphere - Kim, Jeong-In; Kubota, Shusei; Natsui, Shungo; Iwanaga, Taiki; Miki, Yuji; Nogami, Hiroshi (Chemical engineering science, 2023)
[Display omitted] •3D model was developed to analyze reduction of irregularly shaped iron-ore particles.•Existing models were favorable mostly to spherical particles as they are based on 1D.•Actual sintered ore was studied using the model based on the 3D diffusion equation.•The new model was validated using the shrinking core model and experimental data.•Effects of sphericity and pore number on reduction and gas diffusion were assessed. The production of steel, which is achieved by the reduction of iron ores mainly through indirect reduction reactions in a blast furnace, is gradually increasing worldwide. Because the reducing gas diffuses three-dimensionally, irregular particle shapes influence the reduction through differences in the diffusion length. The analysis of actual irregularly shaped iron-ore particles using existing models is difficult because they are primarily effective for 1D systems. Therefore, a novel reduction model based on the 3D diffusion equation that accommodates irregular particle shapes and 3D systems was developed in this study. The established model was validated by reproducing experimental conditions and comparing the quantified effective diffusivity and chemical reaction rate constant using the shrinking core model. In addition, the model was used to investigate the reducing behavior of an actual sintered-ore particle and the effects of particle sphericity and macro pore content. The sintered-ore particle had a higher reduction rate than that of a spherical equivalent with the same volume because sections of the surface with shorter diffusion lengths facilitated the gas diffusion. Additionally, the particle sphericity was determined to be inversely proportional to the reduction rate because the rate of gas diffusion into the particle depended on the diffusion length. With respect to porous particles, the gas was found to readily diffuse into the particles through pores, leading to a higher reduction rate for higher pore numbers. Overall, the gas diffusion was confirmed to drive the reduction reaction.